Effect of Synthetic Cell-Penetrating Peptides on TrkA Activity in PC12 Cells - Munetaka Hirose; Mayumi Takatori; Yoshihiro Kuroda; Mineo Abe; Eri Murata; Tetsuro Isada; Koyo Ueda; Kenji Shigemi; Masayuki Shibazaki; Fumihiro Shimizu; Masashi Hirata; Keita Fukazawa; et al. (Elsevier, 2008)
As TrkA, a high-affinity receptor of nerve growth factor (NGF), is a potential target for relieving uncontrolled inflammatory pain, an effective inhibitor of TrkA has been required for pain management. To identify a specific inhibitor of TrkA activity, we designed cell-penetrating peptides combined with amino-acid sequences in the activation loop of TrkA to antagonize tyrosine kinase activity. To select a peptide inhibiting TrkA activity, we examined the effect of cell-penetrating peptides on tyrosine kinase activity of recombinant TrkA in vitro and studied their effects on NGF-stimulated neurite outgrowth and protein phosphorylation in PC12 cells. Thereafter we investigated the effect of the selected peptide on NGF-stimulated TrkA activity and the expression of transient receptor potential channel 1 in PC12 cells. The selected peptide inhibited TrkA activity, but did not inhibit tyrosine kinase activities of other receptor-type tyrosine kinases in vitro. It also suppressed NGF-stimulated responses in PC12 cells. The selected synthetic cell-penetrating peptide antagonizing TrkA function would be a candidate for inflammatory pain therapy. Keywords:: cell-penetrating peptide, nerve growth factor (NGF), Tat, TrkA, tyrosine phosphorylation